Perfecting the Conscience of Man - Abrams, Charles (Tufts Archival Research Center, 2006)
Charles Abrams tells of his faith in man despite his frequent uncertainty when confronted with the realities of war, greed and other instances of human weakness. However, he remains devoted to the ability of man to rely on his conscience to someday improve and perfect the world in which we live.